ASSETS AND LIABILITIES DEPENDENCE: EVIDENCE FROM AN EUROPEAN SAMPLE OF BANKS - Cociuba Mihail Ioan; Trenca Ioan; Zapodeanu Daniela (Annals of the University of Oradea: Economic Science, 2014)
In this paper we analyzed the correlation between asset and liabilities using the canonical correlation method, in the case of correlation we analyze the interdependence between two variables, by using canonical correlation analyses we study the interdependence between two groups of variables, X consisting of p variables and Y with q variables from which the best linear combination can be constructed to maximize the correlation between X and Y. While on the financial markets the relation between variables may be linear or non-linear and although canonical correlation analyses only the linear combination of variables it is a more efficient tool than then simple correlation.The asset group which we analyze is composed of different types of loans, derivatives and other earning assets, while in the group of liabilities we have deposits (short and long term), interest bearing liabilities and trading liabilities. We find that the assets and liabilities in the banking sector are directly linked. In the context of the global financial crisis (2007-2008) and the afterwards financial recession this direct correlation between assets and liabilities created a vicious cycle in which the losses from assets had a direct impact on the liabilities which also influenced the levels of assets.The behavior of different variables is important, especially in the financial markets, mainly due to the structure of financial markets. The banking sector and the systemic risk associated with it can affect the financial system and even the whole economy so the study of the correlation of assets and liabilities may give us insights on the causes of the financial crises. We use a panel of fifty-nine European banks for the 2004-2011 period and we analyses the correlation between assets and liabilities. We find that there exists a direct and strong connection between different classes of assets held by banks and the structure of liabilities. The impact of the economic crisis on the banking sector has shown that this kind of connection between the structure of assets and liabilities is not the best choice because a negative fluctuation in assets generates a negative impact on the structure of liabilities. The direct connection between assets and liabilities amplifies the systemic risk of the banking sector and can also have an impact on other markets due to their spillover effects.